Comparison of clinical and functional outcomes in patients operated with standard offset stem versus high offset stem in total hip replacement: a retrospective study - Avhad, Tanmay A.; Gunay, Siddharth; Naik, Ketan; Syed, Zafar; Chaudhary, Arif (International Journal of Research in Orthopaedics, 2024)
Background: Femoral offset restoration in total hip replacement is crucial for normal anatomy and reduced joint forces, with potential implications for implant longevity and complications. This study compares standard and high offset stem total hip replacement outcomes for better restoration of native offset, also to improve understanding of clinical and functional outcomes particularly regarding implant selection in total hip replacements. Methods: The study will include 40 patients who underwent THR, divided into standard offset and high offset stem groups. Preoperative data, including history and clinical examination, was collected. Post-operative recovery, satisfaction, and pain levels will be assessed through serial follow-ups at 6, 12, and 18 weeks, along with clinical improvement measured by Harris hip score. Analysis at 18 weeks will evaluate the outcomes of standard vs. high offset stem surgeries. Results: Group A exhibited significantly higher proportions of patients with a Harris hip score >90 (excellent) compared to Group B (70% vs. 25%) and significantly lower proportions with scores indicating poor, fair, and good outcomes (<70: 0% vs. 10%, 70-79: 5% vs. 15%, 80-89: 25% vs. 50%, respectively; p=0.02). Conclusions: This study confirms that increasing femoral offset with high-offset stems improves functional outcomes and biomechanics in total hip arthroplasty, emphasizing the need for patient-specific anatomical consideration.